2008
DOI: 10.1016/s1885-5857(08)60212-1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Metabolic Syndrome, and Diabetes: Cardiovascular Implications and Therapy

Abstract: Obesity, metabolic syndrome, and type-2 diabetes mellitus are 3 interrelated conditions that share a number of pathophysiological mechanisms and that are frequently observed to lead, in succession, to cardiovascular complications. The fact that their prevalence is increasing alarmingly should prompt all healthcare professionals urgently to implement measures to prevent these complications. The most effective, though also the least adopted, are those related to lifestyle modification. Drug treatment targeted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 60 publications
1
26
0
6
Order By: Relevance
“…Diabetes mellitus, commonly known as diabetes is one of the most prevalent metabolic diseases worldwide with incidence predicted to reach 552 million by 2030 . Resveratrol has shown potential to control metabolic diseases including diabetes, obesity, and metabolic syndrome (MS) …”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…Diabetes mellitus, commonly known as diabetes is one of the most prevalent metabolic diseases worldwide with incidence predicted to reach 552 million by 2030 . Resveratrol has shown potential to control metabolic diseases including diabetes, obesity, and metabolic syndrome (MS) …”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…In the present study, all animal groups showed similar weight gain and chow intake. There is evidence that excess body adiposity can lead to a worsening of cardiovascular risk factors, including dyslipidemia [51,52], making the control of such variables extremely relevant in order to guarantee a correct interpretation of the results, avoiding, for example, an erroneous attribution of lipid profile alteration to a surgical procedure on the spleen. Some authors have increased fat content in rat chow during the post-splenectomy period in order to induce hyperlipidemia and emphasize possible alterations in the lipid profile by adding cholesterol to the commercial chow [9,17,43].…”
Section: Discussionmentioning
confidence: 99%
“…Как правило, СД 2-го типа ассоциируется с избыточной массой тела и ожирением у пациентов [13,17]. В настоящее время жировая ткань рассматривается не как инертное депо липидов в организме, а как эндокринный орган, секретирующий в кровь большое количество цитокинов и хемокинов [30].…”
Section: иммунитет и сердце при диабетеunclassified